PENGARUH KEGIATAN ORGANISASI SISWA INTRA SEKOLAH (OSIS) TERHADAP HASIL BELAJAR PADA MATA PELAJARAN EKONOMI KELAS XI DI SMA NEGERI 1 BONEPANTAI - Piyohu, Belviana; Mahmud, Melizubaida; Maruwae, Abdulrahim; Bahsoan, Agil; Halid, Risca Marsanti (Journal of Economic and Business Education, 2025)
The purpose of this study was to determine whether there was an influence of OSIS on student learning outcomes. This study used a descriptive quantitative approach with a sample size of 35 people. The instrument used was a questionnaire. The data analysis technique used was simple linear regression analysis. Based on the results of the data analysis, it is known that there is a significant influence of 51.2% of the variability regarding the variable of Student Learning Outcomes in the Economics Subject of class XI at SMA Negeri 1 Bonepantai which can be explained by the OSIS Activity variable, while the remaining 48.8% is influenced by other variables not examined in this study.